The Effect of Board Effectiveness on Firm Performance with Sustainability Disclosure as Mediating Variable - Butar Butar, Dea Tiara Moonalisa; Winny, Winny; Ramadan, Mariska (Profesional Muda Cendekia Publishing, 2025)
Board effectiveness plays a pivotal role in shaping the performance of firms listed on the Indonesian Stock Exchange (IDX). This research examines the effectiveness of the board of directors on firm performance of companies listed on the Indonesian Stock Exchange (IDX), which is mediated by sustainability disclosure. This research used data from 2020 to 2022, with 105 data from 35 companies listed on the IDX. The results showed that board effectiveness has a positive effect on firm performance. Furthermore, the findings indicate that sustainability disclosure does not significantly affect firm performance, and sustainability disclosure cannot be used as a mediating variable in this research. This research has implications for expanding insight, specifically for managers, investors, and regulators – especially those who aim to improve firm performance in emerging markets.